OeBAS and CYP716C67 catalyze the biosynthesis of health-beneficial triterpenoids in olive (Olea europaea) fruits - Alagna, Fiammetta (The New phytologist, 2023)
© 2023 The Authors New Phytologist © 2023 New Phytologist Foundation.